The Influence of Customer Experience on Repurchase Intention Mediated by Customer Satisfaction: A Case Study of Ultra Milk Consumers in Cimahi, Indonesia - Nurrahim, Fadila; Nurtjahjadi, Edi (Darul Yasin Al Sys, 2025)
This study investigates the mediating role of customer satisfaction in the relationship between customer experience and repurchase intention within the competitive packaged dairy industry, with a focus on Ultra Milk consumers in Cimahi, Indonesia. Despite its importance for consumer loyalty, this mediating effect remains underexplored. The research adopts a quantitative design, using purposive sampling to select 105 respondents who had consumed Ultra Milk in the past three months. Data were collected through structured questionnaires and analyzed using regression analysis and Sobel tests with SPSS software. Results indicate that customer experience has a significant positive effect on customer satisfaction, and both factors significantly influence repurchase intention. Moreover, customer satisfaction mediates the relationship between customer experience and repurchase intention, underscoring the psychological dimension of satisfaction in converting positive experiences into loyalty. The findings reinforce the experiential–satisfaction–loyalty framework and align with behavioral theories of consumer decision-making. The study concludes that enhancing customer experience is essential for driving repurchase behavior, especially when complemented by satisfaction. The implications include theoretical contributions to consumer behavior research by extending empirical insights into mediating effects, as well as practical recommendations for PT. Ultra Jaya and other dairy marketers to invest in strategies that enrich consumer experience and satisfaction to foster long-term loyalty. Future research is recommended to employ longitudinal designs and examine moderating variables such as brand trust and price sensitivity.